Content, Language and Method Integrated Teacher Training (CLMITT) in Training Teachers of English as a Foreign Language (EFL) and Beyond - Agnes Orosz (International Journal of Pedagogy and Teacher Education, 2018)
Content, Language and Method Integrated Teacher Training (CLMITT) is an educational model for teacher training developed by the author. It refers to an approach where trainees learn teaching methodologies through experiencing them while simultaneously integrating English language development into the training process. CLMITT can be used to train teachers in any context where the course content includes teaching strategies, skills, approaches or methods and where trainees also need to learn English (or another foreign language). Therefore, it is an ideal approach for training non-native English speaker teachers. Applying CLMITT involves the teacher trainer teaching a classroom method or technique by using that method itself during training sessions while using materials about that method. In this way, the content of the session and the method used to teach the session are the same, and trainees are not only learning about a teaching model or strategy but also experiencing it in action from a student perspective at the same time. In addition, they are also improving their English, since the whole exercise takes place in English. CLMITT can be applied in Initial Teacher Training (ITT) Programs as well as Continuous Professional Development courses. Trainee feedback after a CLMITT session showed that students felt it provided them with a much deeper understanding of the methods, approaches and strategies covered, while at the same time improving their English during the process.